Southeast Asia : On a shoestring - Williams, China (Dublin : Lonely Planet, 2016)
Lonely Planet: The world's number one travel guide publisher* Lonely Planet's Southeast Asia on a Shoestring is your passport to having big experiences on a small budget, offering the most relevant, up-to-date advice on what to see and skip, what hidden discoveries await you and how to optimise your budget for an extended continental trip. Watch the sun rise over Cambodia's temples of Angkor; hang out, hit the beach and learn to cook in Vietnam's cosmopolitan, buzzing Hoi An; and kayak around the turquoise waters of Laos' Si Phan Don. All with your trusted travel companion. Inside Lonely Planet's Southeast Asia on a Shoestring: - Budget-oriented recommendations with honest reviews - eating, sleeping, sightseeing, going out, hidden gems that most guidebooks miss - Extensive planning tools and budget calculators - Highlights and itineraries help you tailor your trip to your personal needs and interests - Insider tips to save time and money and get around like a local, avoiding crowds and trouble spots - Essential info at your fingertips - hours of operation, phone numbers, websites, transit tips, prices - Cultural insights provide a richer, more rewarding travel experience - covering history, art, literature, cinema, landscapes - Colour maps and images throughout - Covers Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, Philippines, Thailand, Timor-Leste, Singapore, Vietnam - Useful features: First Time Southeast Asia, Big Adventures Small Budget, Off the Beaten Track, Border Crossing, Splurge, and Responsible Travel eBook Features: (Best viewed on tablet devices and smartphones) - Downloadable PDF and offline maps prevent roaming and data charges - Effortlessly navigate and jump between maps and reviews - Add notes to personalise your guidebook experience - Seamlessly flip between pages - Bookmarks and speedy search capabilities get you to key pages in a flash - Embedded links to recommendations' websites - Zoom-in maps and images - Inbuilt dictionary for quick referencing The Perfect Choice: Lonely Planet's Southeast Asia on a shoestringis perfect for budget- and value-conscious travellers taking a big trip, and is packed with amazing sights and experiences, savvy tips and recommendations.
Keywords: Travel Guide -- Southeast AsiaGuidebooks